Distinct Distribution of RTN1A in Immune Cells in Mouse Skin and Lymphoid Organs - Cichoń, Małgorzata Anna; Klas, Katharina; Buchberger, Maria; Hammer, Martina; Seré, Kristin; Zenke, Martin; Tschachler, Erwin; Elbe-Bürger, Adelheid (Frontiers in Cell and Developmental Biology, 2021)
The endoplasmic reticulum-associated protein reticulon 1A (RTN1A) is primarily expressed in neuronal tissues but was recently identified also specifically in cells of the dendritic cell (DC) lineage, including epidermal Langerhans cells (LCs) and dermal DCs in human skin. In this study, we found that in mice major histocompatibility complex class II (MHCII)+CD207+ LCs but not dermal DCs express RTN1A. Further, RTN1A expression was identified in CD45+MHCII+CD207+ cells of the lymph node and spleen but not in the thymus. Of note, RTN1A was expressed in CD207low LCs in adult skin as well as emigrated LCs and DCs in lymph nodes and marginally in CD207hi cells. Ontogeny studies revealed that RTN1A expression occurred before the appearance of the LC markers MHCII and CD207 in LC precursors, while dermal DC and T cell precursors remained negative during skin development. Analogous to the expression of RTN1A in neural tissue, we identified expression of RTN1A in skin nerves. Immunostaining revealed co-localisation of RTN1A with nerve neurofilaments only in fetal but not in newborn or adult dermis. Our findings suggest that RTN1A might be involved in the LC differentiation process given its early expression in LC precursors and stable expression onwards. Further analysis of the RTN1A expression pattern will enable the elucidation of the functional roles of RTN1A in both the immune and the nervous system of the skin.